Legal Malpractice: The Profession's Dirty Little Secret - Ramos, Manuel R. (1994)
Legal malpractice is a taboo subject. It has been ignored by the legal profession,' law schools, mandatory continuing legal education ( CLE ) programs, and even by scholarly' and lay publications. Unfortunately, our perception of legal malpractice, up until now, has been highly distorted by secretive insurance companies, confidential settlement agreements, and a questionable American Bar Association ( ABA ) Study. Nonetheless, sharply contrasting portraits of legal malpractice have emerged: either it is just a minor problem of weeding out a few bad apples, or it is the tip of an iceberg, ready to overwhelm the legal profession. The ABA Study has fostered the minor problem portrait of legal malpractice. Various books, scholarly journals, bar publications, the lay media and even the anti-lawyer consumer group, Help Abolish Legal Tyranny ( HALT ), have uncritically accepted the ABA Study. As noted by HALT, the overwhelming consensus is that, even though someone may be able to locate an attorney who will sue another attorney, extremely few clients ever receive compensation over $1,000, and malpractice cases are hard to win. ' The widely accepted ABA Study has thus become the statistical foundation of the few bad apples portrait of legal malpractice. According to the ABA Study, only between 1.0 and 2.6 percent of lawyers each year face a claim or lawsuit for legal malpractice. A full sixty-seven percent of claimants or plaintiffs receive no compensation, seventy percent of those who do settle receive less than $1,000, and only one percent of those who go to trial win. The ABA Study also reports that almost eighty percent of the claims are against solo practitioners or small law firms of two to five lawyers. Personal injury-plaintiff work (25%) and real estate matters (23%) account for most of the malpractice